Management of care in primary health care: practices and challenges from the eyes of nurses and managers (Research, Society and Development, 2021)
The practices and challenges of health care management have been delineated as a new paradigm in the organization of the health care network, supported by a theoretical-scientific framework capable of mediating the complex relationships of the needs demanded by users of the health system. The aim of this research was to analyze the practices and challenges of care management in primary health care from the eyes of nurses and managers of Primary Health Care. Its method was a descriptive-exploratory research with a qualitative approach. Data collection occurred through interviews with 55 nurses and 9 PHC managers from a municipality in the interior of Ceará and analyzed in the light of the content analysis technique, in its thematic modality. As results, the study showed three categories: Slow ness of public management; Oppressive work process; and, Spraying and breakage of the assistance. It is concluded that the health practices and the challenges evidenced can be drivers of transformations, through the development of programmed management actions collectively, in line with the local reality of each context.